Self-justification for opportunistic purchasing behavior in strategic supplier relationships. Issue 2 (10th December 2018) - Gelderman, Cees J.; Mampaey, Jelle; Semeijn, Janjaap; Verhappen, Mark
Abstract : Purpose: This study aims to get a deeper understanding of one of the antecedents of opportunistic behavior in strategic supplier relationships at the individual level of analysis. The authors specifically focus on self-justification, which could be seen as a mechanism that relaxes the moral scruples of purchasing professionals and, hence, facilitates actual opportunistic behavior. Design/methodology/approach: The critical incident technique was deployed to interview purchasing professionals in the Netherlands about their personal opportunistic behavior in strategic supplier relationships. This resulted in rich autobiographical accounts of 29 critical incidents of opportunistic behavior. The data were analyzed through the lens of the self-justification theory. Findings: The study identified a set of self-justification strategies underlying opportunistic purchasing behavior in strategic supplier relationships. Opportunistic professionals tended to deploy six strategies: acknowledgement, denial, rationalization, attributional egotism, sense of entitlement and ego aggrandizement. Research limitations/implications: This study is limited to Dutch industrial purchasers and was exploratory by nature. Future research could extend the perspective to other sectors, cultures and professional roles. Practical implications: The study draws attention to radically new interventions at the individual level of analysis. To understand and minimize opportunistic behavior in strategic supplier relationships, organizations should acknowledge and address the important issue of self-justifications of purchasing professionals. Originality/value: In contrast to the existing literature at the firm level of analysis, this study sheds new light on the antecedents of buyer opportunism from an alternative theoretical perspective at the individual level of analysis. The authors do not draw on the narrow perspective of personality psychology, but rather focus on the role of self-justification as an antecedent of buyer opportunism in strategic supplier relationships.